PENGARUH CELEBRITY ENDORSER, BRAND IMAGE DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK EMINA COSMETICS (Survei pada Mahasiswa Fakultas Ekonomi Universitas Slamet Riyadi Surakarta) - Ayu Novalia; Rahayu Triastity; Sumaryanto Sumaryanto (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the significance of the influence of celebrity endorsers, brand image and brand trust on purchasing decisions on Emina Cosmetics products. This type of research is a survey of students of the Faculty of Economics, University of Slamet Riyadi Surakarta. The type of data used is quantitative data and qualitative data. Data sources using primary data sources and secondary data. The population in this study were students who used Emina Cosmetics in the Faculty of Economics at Slamet Riyadi University in Surakarta with a sample of 100 people and the sampling technique used purposive sampling. Data collection techniques using questionnaires, observation and literature study. Data analysis techniques using the instrument test, classical assumption test, descriptive analysis, multiple linear regression analysis, t test, F test, and the coefficient of determination. The results of this study indicate that celebrity endorsers have no significant effect on purchasing decisions, brand image has a significant effect on purchasing decisions and brand trust has a significant effect on purchasing decisions.